STRATEGI MENINGKATKAN LOYALITAS MELALUI KEPUASAN PELANGGAN (Studi Produk Kartu Seluler PraBayar Mentari-Indosat Wilayah Lampung) - Victor Marindra Ardianto (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
In marketing, there is no doubt that customer loyalty is essential. Marketers will always try tokeep their customers last or even forever if it’s possible. Therefore, this research tries to exam thefactors impacting on customer loyalty. The predicted factors are: service quality, product quality,price, switching cost and customer satisfaction. Data about those variable was collected byconducting interviews with questionnaire to 135 respondents. The data then were being analyzedusing structural Equation Modeling (SEM) Method.With SEM method to test the hypothesis, the result shows that service quality have apositive impact on customer satisfaction, product quality have a positive impact on customersatisfaction, product price have a positive impact on the customer satisfaction, customer satisfactionhave a positive impact on switching cost, switching cost have a positive impact on customer loyalty.